2013
DOI: 10.1152/japplphysiol.00606.2013
|View full text |Cite
|
Sign up to set email alerts
|

AltitudeOmics: on the consequences of high-altitude acclimatization for the development of fatigue during locomotor exercise in humans

Abstract: The development of muscle fatigue is oxygen (O2)-delivery sensitive [arterial O2 content (CaO2) × limb blood flow (QL)]. Locomotor exercise in acute hypoxia (AH) is, compared with sea level (SL), associated with reduced CaO2 and exaggerated inspiratory muscle work (Winsp), which impairs QL, both of which exacerbate fatigue individually by compromising O2 delivery. Since chronic hypoxia (CH) normalizes CaO2 but exacerbates Winsp, we investigated the consequences of a 14-day exposure to high altitude on exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 59 publications
4
61
0
1
Order By: Relevance
“…An excellent level of reliability was evident for measures of neuromuscular function pre-exercise (Table 2), which is in line with the previous work from our laboratory (Goodall et al 2015b;Thomas et al 2015), and importantly, enabled us to detect significant changes throughout the soccer-specific exercise. Similar reliability coefficients have been demonstrated in unfatigued states for both upper (Lee et al 2008;Madsen 1996;Taylor et al 1996) and lower limb (Amann et al 2013;Bachasson et al 2013;Place et al 2007;Todd et al 2004) muscle groups, but the reliability of the fatigue response following locomotor exercise is unknown. The fatigue response was consistent across repeated trials of the SMS, though the variability in the response tended to increase with exercise duration, with most variable responses found at the ET assessment point.…”
Section: Discussionmentioning
confidence: 60%
“…An excellent level of reliability was evident for measures of neuromuscular function pre-exercise (Table 2), which is in line with the previous work from our laboratory (Goodall et al 2015b;Thomas et al 2015), and importantly, enabled us to detect significant changes throughout the soccer-specific exercise. Similar reliability coefficients have been demonstrated in unfatigued states for both upper (Lee et al 2008;Madsen 1996;Taylor et al 1996) and lower limb (Amann et al 2013;Bachasson et al 2013;Place et al 2007;Todd et al 2004) muscle groups, but the reliability of the fatigue response following locomotor exercise is unknown. The fatigue response was consistent across repeated trials of the SMS, though the variability in the response tended to increase with exercise duration, with most variable responses found at the ET assessment point.…”
Section: Discussionmentioning
confidence: 60%
“…Following exhaustive constant-load cycling (*50% normoxic power output) in acute hypoxia (FIO 2 : 0.105), Amann et al (2013) found that both potentiated quadriceps twitch force and maximal voluntary contraction force were reduced compared to pre-exercise values ( Fig. 2A).…”
Section: Accelerated Peripheral Fatigue Development In Hypoxiamentioning
confidence: 93%
“…The resulting reduction in cerebral blood flow, coupled with reduced CaO 2 , lowers cerebral DO 2 and tissue oxygenation . The subsequent reduction in cerebral tissue oxygenation, combined with increased group III/IV phrenic and muscle afferents' discharge, exacerbates the development of central fatigue and lowers central motor drive during exercise in hypoxia Amann et al, 2013). CaO 2 , arterial O 2 content; DO 2 , oxygen delivery.…”
Section: Limiting Role Of Cerebral Oxygenationmentioning
confidence: 99%
“…Less is known about the mechanism(s) of fatigue during locomotor exercise in chronic hypoxia. We recently reported the accelerated development of peripheral fatigue after locomotor exercise in acute hypoxia to be similar after a period of acclimatisation (14 days) to high altitude; conversely, the level of central fatigue was attenuated (Amann et al , 2013). The measure of central fatigue, however, was determined using peripheral stimulation and the responsiveness of the brain-to-muscle pathway after a period of chronic hypoxia remains unknown.…”
Section: Introductionmentioning
confidence: 99%